Adamantyl‐ and Furanyl‐Protected Nanoscale Silver Sulfide Clusters. Issue 29 (14th June 2016) - Bestgen, Sebastian; Yang, Xiaoxun; Issac, Ibrahim; Fuhr, Olaf; Roesky, Peter W.; Fenske, Dieter
Abstract: The silver salts of 1‐adamantanethiol (AdSH) and furan‐2‐ylmethanethiol (FurCH2 SH) were successfully applied as building blocks for ligand‐protected Ag2 S nanoclusters. The reaction of the silver thiolates [AgSAd] x and [AgSCH2 Fur] x with S(SiMe3 )2 and 1, 5‐bis(diphenylphosphino)pentane (dpppt) afforded three different clusters with 58, 94 and, 190 silver atoms. The intensely colored compounds [Ag58 S13 (SAd)32 ] (1 ), [Ag94 S34 (SAd)26 (dpppt)6 ] (2 ), and [Ag190 S58 (SCH2 Fur)74 (dpppt)8 ] (3 ) were structurally characterized by single‐crystal X‐ray diffraction and exhibit different cluster core geometries and ligand shells. The diameters of the well‐defined sphere‐shaped nanoclusters range from 2.2 nm to 3.5 nm. Abstract : Silver chalcogenide clusters : The reactions of the silver thiolates [AgSAd] x and [AgSCH2 Fur] x with S(SiMe3 )2 and a bidentate phosphine afford three different clusters with 58, 94, and 190 silver atoms. The intensely colored compounds [Ag58 S13 (SAd)32 ], [Ag94 S34 (SAd)26 (dpppt)6 ], and [Ag190 S58 (SCH2 Fur)74 (dpppt)8 ] were structurally characterized by single‐crystal X‐ray crystallography. The diameters of the well‐defined sphere‐shaped nanoclusters range from 2.2 nm to 3.5 nm.